Identical twins with Alzheimer's disease. Issue 5 (May 1983) - Kilpatrick, C; Burns, R; Blumbergs, P C
Abstract : Genetically proven identical twin sisters with Alzheimer's disease are reported. Both sisters at the age of fifty years developed a dementing illness. Their mother and maternal grandmother developed at the same age a similar illness. It is suggested that in some cases of familial Alzheimer's disease the condition is inherited by a single mutant gene.